2009
DOI: 10.1680/adcr.9.00003
|View full text |Cite
|
Sign up to set email alerts
|

Setting and strength development of magnesium phosphate cement paste

Abstract: Magnesium phosphate cement (MPC) paste is prepared by mixing dead-burned magnesia powder and potassium di-hydrogen phosphate with a proper proportion of water. The paste demonstrates superior performance such as fast setting, high early-strength, low shrinkage and good bonding which makes MPC suitable for applications in the rapid repair of infrastructures. However, it has been found that MPC easily sets in a few minutes and thus causes difficulties in manipulation. Therefore, how to retard and control the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Potassium dihydrogen phosphate (KH 2 PO 4 ) has recently been identified as a good candidate for replacing ammonium phosphate [16]. Previous research on MPC prepared with KH 2 PO 4 indicated that the performance of composite was mainly influenced by the reactivity of magnesia, the molar ratio of magnesia-phosphate (M/P), and the retarder and water content [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium dihydrogen phosphate (KH 2 PO 4 ) has recently been identified as a good candidate for replacing ammonium phosphate [16]. Previous research on MPC prepared with KH 2 PO 4 indicated that the performance of composite was mainly influenced by the reactivity of magnesia, the molar ratio of magnesia-phosphate (M/P), and the retarder and water content [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Other than the raw materials which can strongly affect the setting course of MPC, the properties of cement paste can be significantly influenced by the mixture proportions including the molar ratio of magnesium to phosphate (M/P), water content, species and amount of retarder, and curing conditions, etc. [Yang and Wu, 1999;Ding andLi, 2005b and2005c;Paceagiu and Georgescu, 2008;Qiao, et al 2009a and2009b. ] Although the theoretical M/P value is 1 according to the Eq.…”
Section: Parameters Affecting the Properties Of The Cementmentioning
confidence: 99%
“…CaF 2 ) is added to an inorganic solidified foam system, aluminium oxide (Al 2 O 3 ), coming from the admixture, could react with gypsum to form ettringite crystals (AFt) immediately; these will adhere to the particle surface (Qiao et al, 2009). At the same time, the consumption of gypsum accelerates the pace of tricalcium silicate (C 3 S) hydration, forming a small amount of fibrous calcium silicate hydrate filling among the cement particles.…”
Section: Setting Propertymentioning
confidence: 99%